ProTAME Arrest in Mammalian Oocytes and Embryos Does Not Require Spindle Assembly Checkpoint Activity - Radonova, Lenka; Svobodova, Tereza; Skultety, Michal; Mrkva, Ondrej; Libichova, Lenka; Stein, Paula; Anger, Martin (International journal of molecular sciences, 2019)
In both mitosis and meiosis, metaphase to anaphase transition requires the activity of a ubiquitin ligase known as anaphase promoting complex/cyclosome (APC/C). The activation of APC/C in metaphase is under the control of the checkpoint mechanism, called the spindle assembly checkpoint (SAC), which monitors the correct attachment of all kinetochores to the spindle. It has been shown previously in somatic cells that exposure to a small molecule inhibitor, prodrug tosyl-l-arginine methyl ester (proTAME), resulted in cell cycle arrest in metaphase, with low APC/C activity. Interestingly, some reports have also suggested that the activity of SAC is required for this arrest. We focused on the characterization of proTAME inhibition of cell cycle progression in mammalian oocytes and embryos. Our results show that mammalian oocytes and early cleavage embryos show dose-dependent metaphase arrest after exposure to proTAME. However, in comparison to the somatic cells, we show here that the proTAME-induced arrest in these cells does not require SAC activity. Our results revealed important differences between mammalian oocytes and early embryos and somatic cells in their requirements of SAC for APC/C inhibition. In comparison to the somatic cells, oocytes and embryos show much higher frequency of aneuploidy. Our results are therefore important for understanding chromosome segregation control mechanisms, which might contribute to the premature termination of development or severe developmental and mental disorders of newborns.
Keywords: Cattle; Animals; kontrolní body M fáze buněčného cyklu; skot; vztah mezi dávkou a účinkem léčiva; Female; Embryo, Mammalian; Prodrugs; ženské pohlaví; M Phase Cell Cycle Checkpoints; Oocytes; anafázi podporující komplex; Mice; oocyty; Anaphase-Promoting Complex-Cyclosome; prekurzory léčiv; myši; Tosylarginine Methyl Ester; Dose-Response Relationship, Drug; Embryonic Development; tosylargininmethylester; zvířata; embryonální vývoj; embryo savčí